Goal-directed versus Standard Fluid Therapy to Decrease Ileus after Open Radical Cystectomy: A Prospective Randomized Controlled Trial. (August 2020) - Arslan-Carlon, Vittoria; Tan, Kay See; Dalbagni, Guido; Pedoto, Alessia C.; Herr, Harry W.; Bochner, Bernard H.; Cha, Eugene K.; Donahue, Timothy F.; Fischer, Mary; Donat, S. Machele
Abstract : Background: Postoperative ileus is a common complication of intraabdominal surgeries, including radical cystectomy with reported rates as high as 32%. Perioperative fluid administration has been associated with improvement in postoperative ileus rates, but it is difficult to generalize because earlier studies lacked standardized definitions of postoperative ileus and other relevant outcomes. The hypothesis was that targeted individualized perioperative fluid management would improve postoperative ileus in patients receiving radical cystectomy. Methods: This is a parallel-arm, double-blinded, single-center randomized trial of goal-directed fluid therapy versus standard fluid therapy for patients undergoing open radical cystectomy. The primary outcome was postoperative ileus, and the secondary outcome was complications within 30 days post-surgery. Participants were at least 21 yr old, had a maximum body mass index of 45 kg/m 2 and no active atrial fibrillation. The intervention in the goal-directed therapy arm combined preoperative and postoperative stroke volume optimization and intraoperative stroke volume variation minimization to guide fluid administration, using advanced hemodynamic monitoring. Results: Between August 2014 and April 2018, 283 radical cystectomy patients (142 goal-directed fluid therapy and 141 standard fluid therapy) were included in the analysis. Postoperative ileus occurred in 25% (36 of 142) of patients in the goal-directed fluid therapy arm and 21% (30 of 141) of patients in the standard arm (difference in proportions, 4.1%; 95% CI, −5.8 to 13.9; P = 0.418). There was no difference in incidence of high-grade complications between the two arms (20 of 142 [14%] vs. 23 of 141 [16%]; difference in proportions, −2.2%; 95% CI, −10.6 to 6.1; P = 0.602), with the exception of acute kidney injury, which was more frequent in the goal-directed fluid therapy arm (56% [80 of 142] vs. 40% [56 of 141] in the standard arm; difference in proportions, 16.6%; 95% CI, 5.1 to 28.1; P = 0.005; P = 0.170 after adjustment for multiple testing). Conclusions: Goal-directed fluid therapy may not be an effective strategy for lowering the risk of postoperative ileus in patients undergoing open radical cystectomy. Abstract : In a randomized trial of goal-directed versus standard fluid therapy in patients having radical cystectomy, there was no difference in the primary outcome of postoperative ileus. There was no difference between fluid therapies in the secondary outcome of high-grade complications.Supplemental Digital Content is available in the text.